2010
DOI: 10.1016/j.neuroscience.2010.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Increased brain edema in aqp4-null mice in an experimental model of subarachnoid hemorrhage

Abstract: We investigated the role of the glial water channel protein aquaporin-4 in brain edema in a mouse model of subarachnoid haemorrhage in which thirty microliters of blood was injected into the basal cisterns. Brain water content, intracranial pressure and neurological score were compared in wildtype and aquaporin-4 null mice. We also measured blood-brain barrier permeability, and the osmotic permeability of the glia limitans, one of the routes of edema elimination. Wildtype and aquaporin-4 null mice had comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…For example, the early induction of AQP4 by a low dose of thrombin contributes to limitation of the ischemic infarction and formation of edema in mice [48] , and acute vascular disruption is associated with AQP4 loss after transient MCAO in rats [49] . This protective role is also reported in spinal cord compression injury [50] , subarachnoid hemorrhage [51] , intracerebral hemorrhage [52] and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine toxicity [53,54] . These findings demonstrate that AQP4 in astrocytes exerts a beneficial action in pathological conditions.…”
Section: Discussionsupporting
confidence: 60%
“…For example, the early induction of AQP4 by a low dose of thrombin contributes to limitation of the ischemic infarction and formation of edema in mice [48] , and acute vascular disruption is associated with AQP4 loss after transient MCAO in rats [49] . This protective role is also reported in spinal cord compression injury [50] , subarachnoid hemorrhage [51] , intracerebral hemorrhage [52] and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine toxicity [53,54] . These findings demonstrate that AQP4 in astrocytes exerts a beneficial action in pathological conditions.…”
Section: Discussionsupporting
confidence: 60%
“…AQP4 mislocalization partially protects against reperfusion injury after transient middle cerebral artery occlusion in α-syntrophin-null mice (40). AQP4 deficiency in mice appears to worsen the outcome from brain tumor, abscess, cortical freezing, and subarachnoid hemorrhage (41,42). Thus, deficiency or mislocalization of AQP4 protect against cytotoxic (cellular) brain edema with intact blood-brain barrier, whereas AQP4 facilitates clearance of vasogenic (leaky vessel) edema with defective bloodbrain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…9 AQP4 is regarded to have essential roles to maintain BBB integrity in several models of CNS injuries, including spinal cord injury, subarachnoid hemorrhage and ICH. 11,30,31 Our previous study found AQP4 suppressed TJ opening and endothelial cell swelling after ICH when compared with the AQP4 À / À mice group. 11 In addition, AQP4 is believed to be involved in the protective effects of vascular endothelial growth factor (VEGF) and granulocyte colony-stimulating factor on BBB after ICH in our recent work.…”
Section: Erythropoietin Protects Bbb From Disruptionmentioning
confidence: 94%